Identificación de Mastitis subclínica en hatos bovinos lecheros de la Parroquia Pimocha del Cantón Babahoyo - Sánchez Bermúdez, Iliana Judith (2018)
SUMMARY The present investigation was carried out in herds of dairy cattle in the Pimocha parish of the Babahoyo Canton of the Province of Los Ríos with the application of the California Mastitis Test (CMT), considering the very positive (+++), positive cases ( ++), slightly positive (+) when the reaction was immediate with consistent, soft and light gel formation respectively, the traces were considered negative. considering the 736 affected rooms of the 184 animals sampled, 52.17% were positive to the CMT test, with a percentage of 71, 57% in La Delia, 31.91% San Antonio and 32.5% Rodeo Grande. For the evaluation of the risk factors, the Guide to Good Livestock Practices of Technical Production N ° .0217 was considered. R.O.No.842 From November 30, 2012. Agrocalidad, chapters IX, X and XI with the respective literals. 75% compliance for the design and distribution of Article IX was obtained by the dairy herd La Delia, 64.29% San Antonio and 50% Rodeo Grande. The infrastructure and management of the animal according to Article X had a compliance of 64.29% La Delia, 21.43% San Antonio and 28.57% Rodeo Grande. Hygiene conditions for both animals, cowboys, infrastructure referred to in Article IX had a compliance of 50% La Delia, and 0% the remaining herds. Technical aspects that are considered risk factors in the occurrence of subclinical mastitis. The estimate of economic losses as a result of affected quarters, lost, discard milk was $ 8174 in the three dairy herds, corresponding to $ 5684 to the herd with greater number of animals in production this is 95, 1446 $ San Antonio with 47 animals in production and 1044 $ Rodeo Grande, taking into account the cost of drugs and professional services. Keywords: Mastitis, positive cases, good milking practices, economic losses.